Evaluation of the injuries caused by Pachycoris torridus (Scopoli, 1772) (Hemiptera: Scutelleridae) in Jatropha curcas (Linnaeus) (Euphorbiaceae) - Marques Vanderlei Fregadolli, Andrea; Vieira Pires, Edjane; Endres, Laurício; Fregadolli, Fábio Luiz; Perez Ramos, Juan Manuel; Vanderlei Ferreira, Paulo (Revista Ceres, 2025)
The Jatropha curcas species is a perennial plant and easy to manage, being cultivated in many countries because of its high content in oil and the lowest cost of production. This study had as objective to evaluate the injuries caused by the Pachycoris torridus in J. curcas seedlings. Thirty-four days after the planting, 30 J. curcas seedlings were covered with screens and submitted to herbivory of five bugs of the same sex. Morphological and physiological evaluations were conducted 65 days after planting. Seventy-three days after planting, 24 seedlings were submitted to herbivory, using the same methodology as the previous experiment with a quantitative differential of 10 bugs and a batch of 6 plants without insects (control). Evaluations were done 104 days after planting. Male adults (n = 5) of the P. torridus species caused a reduction in the growth and biomass increase in J. curcas seedlings 34 days after planting. After 30 days of herbivores, however the same injuries were not observed in seedlings with 73 days after planting. The injuries (34 days after planting) were considered mild and there was a decrease in the growth and in the biomass accumulation. Upon reaching 73 days after planting, the seedlings became more resistant to the attack of this pest, in such a way that as submitting them to twice the number of insects (n = 10), they did not negatively responded to the herbivory. Finally, the young seedlings were more susceptible to attack, even with low levels of infestation. The pest control should be done when there are signs of infestation at this stage.